Two new species of Metrocoris Mayr (Hemiptera: Heteroptera: Gerridae) from India - Jehamalar, E. Eyarin; Chandra, Kailash (Zootaxa, 2013)
Metrocoris morsei sp. nov., and Metrocoris shillongensis sp. nov., are described from India and compared with known congeners. Metrocoris morsei sp. nov. from Great Nicobar Biosphere Reserve (GNBR), Nicobar Islands, cannot be assigned to any of the known species groups of Metrocoris, so it forms the Metrocoris morsei-group. M. shillongensis sp. nov. from Shillong, Meghalaya, belongs to the M. obscurus-species group and is the second species in this group. The distribution maps of these two new species are given.